Electron driven reactions in sulphur containing biological prototypes - Meneses, Guilherme Ornelas Pimentel (2015)
The interaction of ionising radiation with living tissues may direct or indirectly generate several secondary species with relevant genotoxic potential. Due to recent findings that electrons with energies below the ionisation threshold can effectively damage DNA, radiation-induced damage to biological systems has increasingly come under scrutiny. The exact physico-chemical processes that occur in the first stages of electron induced damage remain to be explained. However, it is also known that free electrons have a short lifetime in the physiological medium. Hence, electron transfer processes studies represent an alternative approach through which the role of "bound" electrons as a source of damage to biological tissues can be further explored. The thesis work consists of studying dissociative electron attachment (DEA) and electron transfer to taurine and thiaproline. DEA measurements were executed in Siedlce University with Prof. Janina Kopyra under COST action MP1002 (Nanoscale insights in ion beam cancer therapy). The electron transfer experiments were conducted in a crossed atom(potassium)-molecule beam arrangement. In these studies the anionic fragmentation patterns were obtained. The results of both mechanisms are shown to be significantly different, unveiling that the damaging potential of secondary electrons can be underestimated. In addition, sulphur atoms appear to strongly influence the dissociation process, demonstrating that certain reactions can be controlled by substitution of sulphur at specific molecular sites.